Reception of Derbyshire principle relating to suit for defamation by central or local government bodies: The ambivalence of Malaysian judiciary - Yaakob, Adnan; Shair Mohamad, Mohd Akram; Ali Mohamed, Ashgar Ali (International Organization Center of Academic Research (OCERINT), 2016)
The tort of defamation offers a person means to clear his name, where the defendant has made a statement attacking the plaintiff’s reputation. In this way defamation seeks to balance the apparent irreconcilable issues of protecting one’s reputation with the right of others to say what they want. A satisfactory balance is critical so that baseless allegations do not ruin lives while allowing a free investigative press to flourish. Defamation takes two forms: libel, in which the statement is of an enduring nature, e.g. written; and slander, where the statement is in a transitory form, e.g. spoken. In either form, the defamation requires a publication of a statement which tends to expose the plaintiff to ridicule or contempt or tends to lower the plaintiff in the minds of right-thinking members of the public. For the most part it is a tort which does not require proof of damage, unless the statement is made in a mere transitory form. The core elements of the tort has remained much the same over the years: the statement must be defamatory, it must refer to the plaintiff and it must be published. The defamation rule applies to all plaintiffs regardless of their nature, including cooperation. However, an important dent to this rule was made in the seminal case of Derbyshire County Council v Times Newspapers Ltd and others [1993] AC 534, by the United Kingdom House of Lords that on the grounds of public interest in the freedom of expression, the courts will not allow free speech to be fettered, by permitting government bodies, whether local or central, to sue for libel. However, person within such organisations may bring proceedings for defamation in their personal capacity if individually identified. Essentially, the Derbyshire principle lays down that under the common law, government bodies, whether central or local, do not have the right to maintain an action for damages for defamation as it would be contrary to the public interest for the organs of government (whether central or local) to have that right because it is of the highest importance that a government body should be open to uninhibited public criticism, and the right to sue for defamation would not only have a chilling effect but would also place an undesirable fetter on the freedom of speech. In the context of Malaysia, the Malaysian judiciary have so far displayed an ambivalent response to the reception of the common law principle laid down in Derbyshire Country Council. Some of the courts of first instance have accepted the principle while others have refused to receive the rule. The Malaysian Court ofAppeal – through at least two cases - have displayed equal ambivalence to the reception of this common law rule. While one Court of Appeal judgment appears to have openly embraced the rule, the Court of Appeal in a recent judgment by a majority have refused to adopt the principle on the cogent ground that Malaysia has two statutory provisions which expressly allow a local or central governing body to sue for defamation, which the common law embodied in Derbyshire cannot abrogate. In light of the foregoing, this paper argues that the Federal Court, the apex court in Malaysia, should decide this critical issue and not let uncertainty in the law prevail. The paper seeks to persuade that while the common law can be abrogated by statute either expressly or by necessary implication, the common law cannot abrogate statutory provisions. Further, while freedom of expression is an important safeguard, it may be more rigorously applied in mature and well developed societies. The primacy of freedom of expression in preventing governmental authorities from suing for defamation may not be a suitable or valid justification in the context of local political situation in Malaysia, where too much freedom of the press with ethical codes not similar to those in the developed democracies, may endanger the reputation of governmental bodies, if freedom of expression were allowed free reign.